Novas interações sociais e a crise dos afetos: estudo sobre as desavenças familiares nos grupos de WhatsApp no contexto da polarização política de 2018 - Andrade, Arlete Nery de (2020)
This paper aims to investigate and understand the events of disagreements in WhatsApp family groups, during the Brazilian presidential campaign of 2018, whose political marketing actions designed a peculiar scenario, not previously experienced, based on in the implantation of fear and hate through the use of digital platforms to spread Fake News. The text covers some theories of communication and information, in order to use references from these two fields, in addition to sociology, philosophy, and linguistics, as a way of supporting the theoretical analysis that involves the theme. For that, the work uses concepts such as Regime of Information Regime, Critical Information Literacy, Regime of Truth and Bios Media. As a special point, the issue of reconfiguring affections was addressed, which, in times of polarization of feelings, were put in check, showing themselves to be volatile and fragile, to the point of shaking structures of solid human groups, such as the family. The major issue that permeates the work is the search for understanding the propensity for conflicts in this environment, and it is based on the assumption that there is a missing element that enhances the occurrence of these conflicts.